Effect of Process Control Agent on the Microstructure of Ni-Based ODS Superalloy Produced by Mechanical Alloying and Sintering - Ju-Yeon Han; Hyunji Kang; Sung-Tag Oh (Archives of Metallurgy and Materials, 2019)
The effects of different types of process control agents (PCA) on the microstructure evolution of Ni-based oxide dispersion-strengthened superalloy have been investigated. Alloy synthesis was performed on elemental powders having a nominal composition of Ni-15Cr-4.5Al-4W-2.5Ti-2Mo-2Ta-0.15Zr-1.1Y2O3 in wt % using high energy ball milling for 5 h. The prepared powders are consolidated by spark plasma sintering at 1000oC. Results indicated that the powder ball-milled with ethanol as PCA showed large particle size, low carbon content and homogeneous distribution of elemental powders compared with the powder by stearic acid. The sintered alloy prepared by ethanol as PCA exhibited a homogeneous microstructure with fine precipitates at the grain boundaries. The microstructural characteristics have been discussed on the basis of function of the PCA.